The family upstairs [compact disc, unabridged] - Jewell, Lisa (Simon & Schuster Audio, 2019)
Gifted musician Clemency Thompson is playing for tourists on the streets of southern France when she receives an urgent text message. Her childhood friend, Lucy, is demanding her immediate return to London. It's happening, says the message. The baby is back. Libby Jones was only six months old when she became an orphan. Now twenty-five, she's astounded to learn of an inheritance that will change her life. A gorgeous, dilapidated townhouse in one of London's poshest neighborhoods has been held in a trust for her all these years. Now it's hers. As Libby investigates the story of her birth parents and the dark legacy of her new home, Clemency and Lucy are headed her way to uncover, and possibly protect, secrets of their own. What really happened in that rambling Chelsea mansion when they were children?